Effectuation elements of entrepreneurial expertise - Sarasvathy, Saras D., 1959- (New horizons in entrepreneurship., 2008)
Explores the theory and techniques of non-predictive control for creating new firms, markets and economic opportunities. This book traces the consequences of effectuation for business management, economics and social philosophy. It is intended for students and scholars of entrepreneurship.